Person- and People-Centered Integrated Health Care for Alcohol Dependence – Whether It Is Real in the Present Moment - Jovanovic, Mirjana; Antunovic, Marko (Frontiers in Public Health, 2016)
Alcohol continues to occupy a leading position in Europe as a popular substance of abuse. Together with cigarette smoking and obesity, alcohol is a major cause of preventable diseases. Harmful use of alcohol is one of the main factors contributing to premature deaths and disability and has a major impact on public health. The consequences of alcohol use on human health are enormous. Additionally, alcohol use can have harmful effects that do not directly affect the person who consumes alcohol (e.g. fetal alcohol syndrome, violations that are related to alcohol use…) Also, the harmful effects and consequences of alcohol use (e.g. acute and chronic illness, injuries in fights, at the workplace, in traffic, violent behavior, and death) create a great burden for the economic development of a society. Unfortunately, confirmed alcoholics that are still drinking are unlikely to be given a life insurance cover. On the other hand, if a person is now a recovering alcoholic with a considerable abstinence period, he/she may hope to get a good life insurance quote. Usually, a year or two is believed to be an adequate amount of time for a person to get a life insurance cover at an average price. However, this is only possible if the alcohol did not cause serious health issues to the person. Furthermore, relapsing after impatient rehabilitation can be viewed as an aggravating factor to get a life insurance. So far the research focused on the effects on the population level, such as the increase in taxes, advertising bans and the implementation of laws that prevent the use of alcohol in traffic. However, it seems that the problem may be viewed at the individual level. In any case, models of treatment should be tailored to the needs of the individual. These models should incorporate the reduction of alcohol intake, but also the path to abstinence. The plan should take into account the different (individual) needs for treatment, with regard to the degree of alcohol dependence and health status, but also include the needs of the family, community and broader society.